2015
DOI: 10.1186/s12933-015-0264-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DPP-4 reduces acute mortality after myocardial infarction with restoration of autophagic response in type 2 diabetic rats

Abstract: BackgroundType 2 diabetes mellitus (T2DM) worsens the outcome after myocardial infarction (MI). Here, we hypothesized that inhibition of dipeptidyl peptidase-4 (DPP-4) improves survival after MI in T2DM by modifying autophagy in the non-infarcted region of the heart.Methods and resultsUnder baseline conditions, there was no significant difference between levels of myocardial autophagy marker proteins in OLETF, a rat model of T2DM, and in LETO, a non-diabetic control. However, in contrast to the response in LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 54 publications
12
65
0
Order By: Relevance
“…Several type 1 diabetic disease models including diabetes‐prone (DP) BB rats and streptozotocin (STZ)‐induced diabetic models have been used to study type 1 diabetes . Type 2 diabetes is characterized by insulin resistance, for which db/db mice, OLETF rats, and ZFDM rats serve as experimental animal models . Among these, the OLETF rat is a useful animal model for type II diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…Several type 1 diabetic disease models including diabetes‐prone (DP) BB rats and streptozotocin (STZ)‐induced diabetic models have been used to study type 1 diabetes . Type 2 diabetes is characterized by insulin resistance, for which db/db mice, OLETF rats, and ZFDM rats serve as experimental animal models . Among these, the OLETF rat is a useful animal model for type II diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…; Murase et al. ). Vehicle‐treated LETO and OLETF and empagliflozin‐treated OLETF were divided into two subgroups depending on whether a sham operation (Sham) or coronary ligation to induce MI was performed.…”
Section: Methodsmentioning
confidence: 97%
“…We found that activation of autophagy, a stress‐responsive intracellular digestion system, in the noninfarcted region is blunted by diabetes, possibly contributing to insufficient mechanical compensation (Murase et al. ). In addition, we found that empagliflozin significantly improved ATP generation together with increased ketone utilization and upregulated superoxide dismutase 2 (SOD2) and catalase expression in the noninfarcted region of the heart after MI in OLETF (Oshima et al.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations